Grundlagen der Informationswissenschaft - Kuhlen, Rainer; Lewandowski, Dirk; Semar, Wolfgang; Womser-Hacker, Christa (De Gruyter, 2022)
The seventh edition of the Principles of Practical Information and Documentation is now called: The Principles of Information Science. The new title does justice to the fact that there is an increasing need to theorize how we deal with knowledge and information in practice, training, and research as well as the development of information skills, in particular in online information services. All articles in the volume have been rewritten.